The Influence of E-Purchasing Effectiveness on Construction Procurement Performance in Bali: The Mediating Role of E-Purchasing Efficiency - Dewa Ayu Dian Regina Permata; Anak Agung Diah Parami Dewi; Dewa Ketut Sudarsana (International Journal Labs, 2026)
The implementation of e-purchasing in construction procurement has been continuously promoted by the Indonesian government. However, Klungkung Regency remains the only regency in Bali Province that has not yet implemented e-purchasing for construction projects. In addition, empirical studies examining the effects of e-purchasing effectiveness and efficiency on construction procurement performance remain limited. This study analyzes the effects of e-purchasing effectiveness and efficiency on construction procurement performance, examines the effect of effectiveness on efficiency, investigates the mediating role of efficiency, and formulates implementation strategies. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were collected through questionnaires distributed to 30 respondents experienced in implementing construction e-purchasing and analyzed using PLS-SEM. Qualitative data were obtained through in-depth interviews with key informants. The results show that e-purchasing effectiveness positively and significantly affects construction procurement performance (?=0.518, t=5.453, p= 0.000). E-purchasing efficiency also has a positive and significant effect on construction procurement performance (?=0.473, t=5.210, p=0.000). Furthermore, effectiveness positively and significantly influences efficiency (?=0.559, t=5.757, p=0.000). Efficiency acts as a complementary partial mediator between effectiveness and construction procurement performance. The strategies for the implementation include expanding construction work items in the Electronic Catalog, increasing vendor participation through outreach, improving the e-purchasing system, and developing technical implementation guidelines. The findings indicate that improving e-purchasing effectiveness and efficiency enhances construction procurement performance by better meeting procurement needs, increasing vendor participation, simplifying procedures, reducing administrative costs, and accelerating procurement processes.